The effect of breathing exercises on fatigue level of COPD patients - Zakerimoghadam M; Shaban M; Kazemnejad A; Tavasoli Kh (Tehran University of Medical Sciences, 2006)
Background & Aim: Fatigue is a premature symptom in the patients suffering from chronic obstructive pulmonary disease. This study was conducted to investigate the effect of breathing exercises on fatigue level of COPD patients. Methods & Materials: This clinical trial is a semi-experimental study. 60 patients suffering COPD which are bedridden at, Tehran university of Medical Sciences hospital wards which have been sampled simply and divided into experience and control group randomly. Data gathering is done by interview and data registration from the files. The data gathering tools are questionnaires, fatigue severity scale (FSS) and respiratory exercise usage checklist. The questionnaire includes to sections of demographic characteristics and patient info. The exercises check list is scaled from 0 to 40 in the way that the maximum amount of usage in 10 days, for 4 daily sessions would be 40 and for the case of usage 0 score is assigned. Fatigue severity scale includes 9 questions with visual diagrams scaled from 0 (Lack of fatigue) to 4 (server fatigue). The gathered data is analysis using SPSS software and the descriptive and deductive statistical methods (Tisuchi, Kai2 and Pearson correlation exam) are used to achieve the research goals. Results: The results show that the average fatigue intensity for the experience group is 40.916 with the standard deviation of 14.4 and for the control group is 52.20 with 8.539 standard deviation after the study and statistical T-exam (p=0.001) indicated that there is a significant difference in fatigue severity between experience and control groups after the study. The findings also showed that the average fatigue severity before (55.766) and after (40.166) using the respiratory exercises in the experience group (p<.001) has enormous difference. While the average fatigue severity in the control group (p=0.002) before (54.166) and after (52.200) the study has a ting difference. Regarding the correlation of using respiratory exercises and the changes in fatigue severity, the Pearson statistical exam showed that there is a significant reverse correlation between using respiratory exercises and fatigue severity (r=-0.593, p=0.001). Conclusion: Based on the research findings it can be concluded that using respiratory exercises is effective in reducing the fatigue in the patients with COPD that also confirms the research assumption and the more the respiratory exercises are used the less is the amount of fatigue in the interfered samples.